The effect of grain moisture on grain loss in mechanized rice harvesting: a case study / Rohaida Mohammad - Mohammad, Rohaida (Faculty of Plantation and Agrotechnology, 2018)
Harvesting is a process to collect the mature rice from the paddy either traditional or modern. Nowadays, the use of combine harvester already used in Malaysia because it operation into ones simultaneously. The key important to apply standard harvesting methods to enable in increase grain yields. However, the grain loss during harvesting paddy shows the high percentage losses. One of the factors that may influence grain loss during harvesting is grain moisture. The purpose of this study to investigate the relationships of effect Grain Moisture and Grain Loss in Malaysia. This is based on the study area at Block C, Sawah Kundang Teluk Rimba 84400 Sg. Mati Ledang Johor, Darul Takzim and the result were interpreted by using Statistical Packages for the Social Science (SPSS) version 20. The Correlation Analysis shows the relationship between the Grain Moisture and Grain Loss is around 0.987 so it around 98% that is indicates there is strong positive correlation. For the Regression Analysis, the point of y-intercept -0.5634 and 0.1116 is Grain Moisture that positively affects the Grain Loss by each unit is 0.5634 near to the straight line in normal distribution. Generally, the findings of the study would be useful guidance for the farmers to predict the grain loss by using grain moisture.